Study activities of high-performing higher education students in the South Central Network - Vera-Cervantes, Eugenia Erica (2025)
Introduction. It is important to learn from students who demonstrate academic success in Higher Education Institutions and to share these experiences with new generations, given that higher education faces a significant challenge related to dropout and academic failure. In this context, study habits are currently a crucial element in academic performance. Objective. To examine the study habits of high-achieving students in the Higher Education Institutions that comprise the ANUIES Central-Southern Region Tutoring Network, with the aim of providing a foundation for future generations of students. Methodology. A quantitative study was conducted using a descriptive, cross-sectional, and comparative approach between high- and low-achieving students in the Network's Higher Education Institutions. A total of 4,995 students participated, identified through the Study Activities Questionnaire (SAC). Results and conclusions. In this research, after analyzing the results regarding the 71 study habits across the 10 dimensions, the habits of students who excel in their grades are announced, which will give higher education institutions the opportunity to generate actions to improve the academic performance of new generations.